Clinical Validation of Calf Circumference with DEXA Scans as a Measure of Muscle Mass to Assess Sarcopenia in Community Settings in Indian Postmenopausal Women - Renuka Malik; Himanshi Goel (Wolters Kluwer Medknow Publications, 2024)
Aims and Objective: To validate calf circumference as a reliable clinical tool for measuring muscle mass in postmenopausal women. Materials and Methods: A cross sectional study done at Ram Manohar Lohia Hospital, New Delhi from February 2023 to September 2023. Thirty postmenopausal women were enrolled for this study. Women with surgical menopause, premature ovarian failure, chronic debilitating illness and morbid obesity were excluded. In these women, muscle mass was measured using calf circumference. Also, Appendicular skeletal muscle index (ASMI), a measure of muscle mass was calculated using DEXA scan (Gold standard). The muscle mass was taken as a parameter by both methods to detect sarcopenia. The collected data was analysed and statistically evaluated to clinically validate calf circumference as a reliable tool for measuring muscle mass in Indian postmenopausal women. Results: In our study, the values at different cut offs of calf circumference was compared to ASMI scoring using gold standard investigation DEXA Scan. The better accuracy was found for the cut off point 32 cm of calf circumference with sensitivity of 100%, specificity of 60%, positive predictive value of 71.4%, negative predictive value of 100% and accuracy of 80%. The prevalence of sarcopenia was found to be 70%. Conclusion: Calf circumference can be used as reliable clinical tool to assess sarcopenia as a measure of muscle mass in Indian postmenopausal women.